Modelling of a Hot Stove for the Blast Furnace - Zetterholm, Jonas (2014)
This thesis was conducted at Luleå University of technology in cooperation with Swerea MEFOS during the spring of 2014. The purpose of this work was to develop a dynamic model for the hot stoves for the blast furnace which is to be used to further optimise the stove operation.To be able to investigate different operating scenarios outside of current operating practices, the model was derived from fundamental heat transfer equations. It was implemented using finite difference approximation of the energy balance in a spreadsheet-based environment. In order to validate the developed model, operational data for a stove at SSAB, Luleå was used and measurements carried out on the stove was compared with model outputs.The developed model showed a good prediction of the flue gas temperature but it did however deviate in the behaviour of the temperature in the heat storing material. This is most likely due to the use of constant properties in the solid material.To illustrate the application of the developed model, a flue gas recirculation scenario was investigated and compared with a reference scenario. The model showed that the flue gas recirculation scenario could sustain the same blast and flame temperature with a decreased total flow through the stove during on-gas. In addition to this the model showed a decrease in flue gas temperature and an increase in hot blast temperature. This increase in hot blast temperature could increase the blast temperature and possibly lower the coke consumption in the blast furnace. In conclusion, this thesis has provided a model which was able to predict the performance of a hot stove for the blast furnace. The model shows the possibility to investigate a new operating scenario currently untested.From the validation of the model there were however some deviations between measured and modelled temperatures. It is recommended to further validate the model on a hot stove where more measurements are carried out and develop the thermophysical properties of the solid materials with the ...